A rapid national survey of terrestrial and semi-aquatic mammals using environmental DNA metabarcoding - Holly A. Broadhurst; Elin E. Smith; Jake M. Jackman; Robert Raynor; Claire Howe; Naiara Guimarães Sales; Allan D. McDevitt (Mammalian Biology, 2026)
Assessing the distribution and diversity of terrestrial and semi-aquatic mammals is fundamental for effective conservation efforts. Environmental DNA (eDNA) metabarcoding has emerged as a rapid and cost-effective method for surveying mammals. It has promising avenues for conducting national surveys and enabling comprehensive assessments of mammalian populations across diverse habitats. We collected eDNA samples from 60 water systems across six regions in England (from north to south), United Kingdom, over a period of up to four days in each region. We detected 26 mammals from five taxonomic orders across all sampling locations, recovering 53–89% of the known mammal community in each region. Our findings underscore the feasibility of utilising eDNA metabarcoding for rapidly surveying mammal populations on a national scale, potentially complementing data from existing surveys/records or implementing in data deficient regions. However, challenges remain for surveying certain species using this method, with varying levels of detectability of key species (e.g. otters) across regions.

Green infrastructure impacts in winegrowing: A systematic map - Ebba Engström; Robert Fish; Caroline Howe; Catherine Matilda Collins; Benjamin J. Roberts; Samuel Watkins; Alexandra Collins (Agriculture, Ecosystems & Environment, 2025)

The unexpected influence of legacy conspecific density dependence - Lukas J. Magee; Joseph A. LaManna; Amy T. Wolf; Robert W. Howe; Yuanming Lu; Denis Valle; Daniel J. B. Smith; Robert Bagchi; David Bauman; Daniel J. Johnson (Ecology Letters, 2024)
When plants die, neighbours escape competition. Living conspecifics could disproportionately benefit because they are freed from negative intraspecific processes; however, if the negative effects of past conspecific neighbours persist, other species might be advantaged, and diversity might be maintained through legacy effects. We examined legacy effects in a mapped forest by modelling the survival of 37,212 trees of 23 species using four neighbourhood properties: living conspecific, living heterospecific, legacy conspecific (dead conspecifics) and legacy heterospecific densities. Legacy conspecific effects proved nearly four times stronger than living conspecific effects; changes in annual survival associated with legacy conspecific density were 1.5% greater than living conspecific effects. Over 90% of species were negatively impacted by legacy conspecific density, compared to 47% by living conspecific density. Our results emphasize that legacies of trees alter community dynamics, revealing that prior research may have underestimated the strength of density dependent interactions by not considering legacy effects.

A review of new and existing non-extractive techniques for monitoring marine protected areas - Ryan McGeady; Robert M. Runya; James S. G. Dooley; John A. Howe; Clive J. Fox; Andrew J. Wheeler; Gerard Summers; Alexander Callaway; Suzanne Beck; Louise S. Brown; Gerard Dooly; Chris McGonigle (Frontiers in Marine Science, 2023)
Ocean biodiversity loss is being driven by several anthropogenic threats and significant efforts are required to halt losses and promote healthy marine ecosystems. The establishment of a network of Marine Protected Areas (MPAs) can help restrict damaging activities and have been recognised as a potential solution to aid marine conservation. When managed correctly they can deliver both ecological and socio-economic benefits. In recent times, MPA designations have increased rapidly while many countries have set future MPA targets for the decades ahead. An integral element of MPA management is adequate monitoring that collects data to assess if conservation objectives are being achieved. Data acquired by monitoring can vary widely as can the techniques employed to collect such data. Ideally, non-destructive and non-invasive methods are preferred to prevent damage to habitats and species, though this may rule out a number of traditional extractive sampling approaches such as dredges and trawls. Moreover, advances in ocean observation technologies enable the collection of large amounts of data at high resolutions, while automated data processing is beginning to make analyses more logistically feasible and less time-consuming. Therefore, developments to existing marine monitoring techniques and new emerging technologies have led to a diverse array of options when choosing to implement an MPA monitoring programme. Here, we present a review of new and existing non-extractive techniques which can be applied to MPA monitoring. We summarise their capabilities, applications, advantages, limitations and possible future developments. The review is intended to aid MPA managers and researchers in determining the suitability of available monitoring techniques based on data requirements and site conditions.

Biogeographic context is related to local scale tree demography, co‐occurrence and functional differentiation - Nathan G. Swenson; Jenny Zambrano; Robert Howe; Amy Wolf (Ecology Letters, 2023)
Identifying the drivers of community structure and dynamics is a major pursuit in ecology. Emphasis is typically placed on the importance of local scale interactions when attempting to explain these fundamental ecological patterns. However, regional scale phenomena are also important predictors. The importance of regional scale context should be more evident in assemblages where multiple species are close to their range margins. Here, we test the importance of regional scale context using data from a temperate forest plot that contains two species groups – one near its northern range limit and one near its southern range limit. We show the proximity of species to their southern or northern range margins is linked to local scale co‐occurrence, similarity in gene expression responses to a key environmental driver, demographic performance and inter‐specific variation in conspecific negative density dependence. In sum, many of the key local scale patterns and processes of interest to community ecologists are linked to biogeographic context that is frequently ignored.

Brain volume in chronic ketamine users — relationship to sub-threshold psychotic symptoms and relevance to schizophrenia - Robert A. Chesters; Fiona Pepper; Celia Morgan; Jonathan D. Cooper; Oliver D. Howes; Anthony C. Vernon; James M. Stone (Psychopharmacology, 2022)
Rationale Ketamine may model aspects of schizophrenia arising through NMDA receptor activity deficits. Although acute ketamine can induce effects resembling both positive and negative psychotic symptoms, chronic use may be a closer model of idiopathic psychosis. Objectives We tested the hypotheses that ketamine users had lower brain volumes, as measured using MRI, and greater sub-threshold psychotic symptoms relative to a poly-drug user control group. Methods Ketamine users (n = 17) and poly-drug using controls (n = 19) were included in the study. All underwent volumetric MRI imaging and measurement of sub-threshold psychotic symptoms using the Comprehensive Assessment of At-Risk Mental State (CAARMS). Freesurfer was used to analyse differences in regional brain volume, cortical surface area and thickness between ketamine users and controls. The relationship between CAARMS ratings and brain volume was also investigated in ketamine users. Results Ketamine users were found to have significantly lower grey matter volumes of the nucleus accumbens, caudate nucleus, cerebellum and total cortex (FDR p < 0.05; Cohen’s d = 0.36–0.75). Within the cortex, ketamine users had significantly lower grey matter volumes within the frontal, temporal and parietal cortices (Cohen’s d 0.7–1.31; FDR p < 0.05). They also had significantly higher sub-threshold psychotic symptoms (p < 0.05). Frequency of ketamine use showed an inverse correlation with cerebellar volume (p < 0.001), but there was no relationship between regional brain volumes and sub-threshold psychotic symptoms. Conclusions Chronic ketamine use may cause lower grey matter volumes as well as inducing sub-threshold psychotic symptoms, although these likely arise through distinct mechanisms.

Characterizing the Effects of Nasal Prong Interfaces on Aerosol Deposition in a Preterm Infant Nasal Model - Karl Bass; Mohammad A. M. Momin; Connor Howe; Ghali Aladwani; Sarah Strickler; Arun V. Kolanjiyil; Michael Hindle; Robert M. DiBlasi; Worth Longest (AAPS PharmSciTech, 2022)
The objective of this study was to characterize the effects of multiple nasal prong interface configurations on nasal depositional loss of pharmaceutical aerosols in a preterm infant nose-throat (NT) airway model. Benchmark in vitro experiments were performed in which a spray-dried powder formulation was delivered to a new preterm NT model with a positive-pressure infant air-jet dry powder inhaler using single- and dual-prong interfaces. These results were used to develop and validate a computational fluid dynamics (CFD) model of aerosol transport and deposition in the NT geometry. The validated CFD model was then used to explore the NT depositional characteristic of multiple prong types and configurations. The CFD model highlighted a turbulent jet effect emanating from the prong(s). Analysis of NT aerosol deposition efficiency curves for a characteristic particle size and delivery flowrate (3 µm and 1.4 L/min (LPM)) revealed little difference in NT aerosol deposition fraction (DF) across the prong insertion depths of 2–5 mm (DF = 16–24%) with the exception of a single prong with 5-mm insertion (DF = 36%). Dual prongs provided a modest reduction in deposition vs. a single aerosol delivery prong at the same flow for insertion depths Graphical Abstract

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A dual compartment cuvette system for correcting scattering in whole-cell absorbance spectroscopy of photosynthetic microorganisms - John R. D. Hervey; Paolo Bombelli; David J. Lea-Smith; Alan K. Hulme; Nathan R. Hulme; Atvinder K. Rullay; Robert Keighley; Christopher J. Howe (Photosynthesis Research, 2022)
Absorption spectroscopy is widely used to determine absorption and transmission spectra of chromophores in solution, in addition to suspensions of particles, including micro-organisms. Light scattering, caused by photons deflected from part or all of the cells or other particles in suspension, results in distortions to the absorption spectra, lost information and poor resolution. A spectrophotometer with an integrating sphere may be used to alleviate this problem. However, these instruments are not universally available in biology laboratories, for reasons such as cost. Here, we describe a novel, rapid, and inexpensive technique that minimises the effect of light scattering when performing whole-cell spectroscopy. This method involves using a custom made dual compartment cuvette containing titanium dioxide in one chamber as a scattering agent. Measurements were conducted of a range of different photosynthetic micro-organisms of varying cell size and morphology, including cyanobacteria, eukaryotic microalgae and a purple non-sulphur bacterium. A concentration of 1 mg ml −1 titanium dioxide, using a spectrophotometer with a slit width of 5 nm, produced spectra for cyanobacteria and microalgae similar (1–4% difference) to those obtained using an integrating sphere. The spectrum > 520 nm was similar to that with an integrating sphere with the purple non-sulphur bacterium. This system produced superior results to those obtained using a recently reported method, the application of the diffusing agent, Scotch™ Magic tape, to the side of the cuvette. The protocol can be completed in an equivalent period of time to standard whole-cell absorbance spectroscopy techniques, and is, in principle, suitable for any dual-beam spectrophotometer.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Addressing the welfare needs of farmed lumpfish: Knowledge gaps, challenges and solutions - Carlos Garcia de Leaniz; Carolina Gutierrez Rabadan; Sara I. Barrento; Rebecca Stringwell; Paul N. Howes; Ben A. Whittaker; Jessica F. Minett; Robert G. Smith; Craig L. Pooley; Ben J. Overland; Leigh Biddiscombe; Richard Lloyd; et al. (Reviews in Aquaculture, 2022)
Lumpfish ( Cyclopterus lumpus L.) are increasingly being used as cleaner fish to control parasitic sea lice, one of the most important threats to salmon farming. However, lumpfish cannot survive feeding solely on sea lice, and their mortality in salmon net‐pens can be high, which has welfare, ethical and economic implications. The industry is under increasing pressure to improve the welfare of lumpfish, but little guidance exists on how this can be achieved. We undertook a knowledge gap and prioritisation exercise using a Delphi approach with participants from the fish farming sector, animal welfare, academia and regulators to assess consensus on the main challenges and potential solutions for improving lumpfish welfare. Consensus among participants on the utility of 5 behavioural and 12 physical welfare indicators was high (87–89%), reliable (Cronbach's alpha = 0.79, 95CI = 0.69–0.92) and independent of participant background. Participants highlighted fin erosion and body damage as the most useful and practical operational welfare indicators, and blood parameters and behavioural indicators as the least practical. Species profiling revealed profound differences between Atlantic salmon and lumpfish in relation to behaviour, habitat preferences, nutritional needs and response to stress, suggesting that applying a common set of welfare standards to both species cohabiting in salmon net‐pens may not work well for lumpfish. Our study offers 16 practical solutions for improving the welfare of lumpfish and illustrates the merits of the Delphi approach for achieving consensus among stakeholders on welfare needs, targeting research where is most needed and generating workable solutions.

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Leveraging a Landscape-Level Monitoring and Assessment Program for Developing Resilient Shorelines throughout the Laurentian Great Lakes - Donald G. Uzarski; Douglas A. Wilcox; Valerie J. Brady; Matthew J. Cooper; Dennis A. Albert; Jan J. H. Ciborowski; Nicholas P. Danz; Anne Garwood; Joseph P. Gathman; Thomas M. Gehring; Greg P. Grabas; Robert W. Howe; et al. (Wetlands, 2019)

The effects of cannabinoid 1 receptor compounds on memory: a meta-analysis and systematic review across species - Faith Borgan; Katherine Beck; Emma Butler; Robert McCutcheon; Mattia Veronese; Anthony Vernon; Oliver D. Howes (Psychopharmacology, 2019)

Environment‐ and trait‐mediated scaling of tree occupancy in forests worldwide - Haibao Ren; Petr Keil; Xiangcheng Mi; Keping Ma; Zhanqing Hao; Wanhui Ye; Luxiang Lin; Renato Valencia; Christine Dawn Fletcher; Duncan W. Thomas; Robert W. Howe; James Lutz; et al. (Global Ecology and Biogeography, 2019)
Aim The relationship between the proportion of sites occupied by a species and the area of a site [occupancy–area relationship (OAR)] offers key information for biodiversity management and has long fascinated ecologists. We quantified the variation in OAR for 3,157 woody species in 17 forest plots worldwide and tested the relative importance of environment and species traits for explaining this variation and evaluated overall model predictive ability. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We used mixed‐effect regression to examine the observed shape of the OAR (its “slope”) against species‐specific and plot‐wide predictors: coarse‐grain occupancy, tree size, plot species richness, energy availability and topographic complexity. Results We found large variation in OAR slopes, and the variation was strongest among species within plots. The OAR slopes showed a latitudinal trend and were steeper near the equator. As predicted, coarse‐grain occupancy and tree size negatively affected OAR slopes, whereas species richness had a positive effect and explained most of the variance between plots. Although hypothesized directionalities were broadly confirmed, traits and environment had relatively limited overall predictive power. Main conclusions These results document the variation of the OAR for 3,157 species at near‐global extent. We found a latitudinal gradient in OAR slopes and confirmed key hypothesized predictors. But at this global extent and over the large set of species analysed, the remaining unexplained variation in OAR slopes was substantial. Nevertheless, this large‐scale empirical analysis of the OAR offers an initial step towards a more general use of OARs for the fine‐scale prediction of species distributions and abundance.

Altered glutamatergic response and functional connectivity in treatment resistant schizophrenia: the effect of riluzole and therapeutic implications - Toby Pillinger; Maria Rogdaki; Robert A. McCutcheon; Pamela Hathway; Alice Egerton; Oliver D. Howes (Psychopharmacology, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Ecological drivers of spatial community dissimilarity, species replacement and species nestedness across temperate forests - Xugao Wang; Thorsten Wiegand; Kristina J. Anderson‐Teixeira; Norman A. Bourg; Zhanqing Hao; Robert Howe; Guangze Jin; David A. Orwig; Marko J. Spasojevic; Shunzhong Wang; Amy Wolf; Jonathan A. Myers (Global Ecology and Biogeography, 2018)
Aims Patterns of spatial community dissimilarity have inspired a large body of theory in ecology and biogeography. Yet key gaps remain in our understanding of the local‐scale ecological processes underlying species replacement and species nestedness, the two fundamental components of spatial community dissimilarity. Here, we examined the relative influence of dispersal limitation, habitat filtering and interspecific species interactions on local‐scale patterns of the replacement and nestedness components in eight stem‐mapped temperate forest mega‐plots at different ontogenetic stages (large versus small trees). Location Eight large (20–35 ha), fully mapped temperate forest plots in northern China and northern U.S.A. Time period 2004–2016. Major taxa studied Woody plants. Methods We combined decomposition of community dissimilarity (based on the Ružička index) and spatial point‐pattern analysis to compare the spatial (i.e., distance‐dependent) replacement and nestedness components of each plot with that expected under five spatially explicit null models representing different hypotheses on community‐assembly mechanisms. Results Our analyses revealed complex results. In all eight forests, spatial community dissimilarity was best explained by species replacement among local tree assemblages and by a null model based on dispersal limitation. In contrast, spatial nestedness for large and small trees was best explained by random placement and habitat filtering, respectively, in addition to dispersal limitation. However, interspecific interactions did not contribute to local replacement and nestedness. Main conclusions Species replacement is the predominant process accounting for spatial community dissimilarity in these temperate forests and caused largely by local‐scale species clustering associated with dispersal limitation. Nestedness, in contrast, is less prevalent and primarily associated with larger variation in local species richness as caused by spatial richness gradients or ‘hotspots’ of local species richness. The novel use of replacement and nestedness measures in point pattern analysis is a promising approach to assess local‐scale biodiversity patterns and to explore their causes.

The role of functional uniqueness and spatial aggregation in explaining rarity in trees - María Natalia Umaña; Xiangcheng Mi; Min Cao; Brian J. Enquist; Zhanqing Hao; Robert Howe; Yoshiko Iida; Daniel Johnson; Luxiang Lin; Xiaojuan Liu; Keping Ma; I‐Fang Sun; et al. (Global Ecology and Biogeography, 2017)
Aim Determining the drivers of species rarity is fundamental for understanding and conserving biodiversity. Rarity of a given species within its community may arise due to exclusion by other ecologically similar species. Conversely, rare species may occupy habitats that are rare in the landscape or they may be ill‐suited to all available habitats. The first mechanism would lead to common and rare species occupying similar ecological space defined by functional traits. The second mechanism would result in common and rare species occupying dissimilar ecological space and spatial aggregation of rare species, either because they are specialists in rare habitats or because rare species tend to be dispersal limited. Here, we quantified the contribution of locally rare species to community functional richness and the spatial aggregation of species across tree communities world‐wide to address these hypotheses. Location Asia and the Americas. Time period 2002 to 2012 (period that considers the censuses for the plots used). Major taxa studied Angiosperm and Gymnosperm trees. Methods We compiled a dataset of functional traits from all the species present in eight tree plots around the world to evaluate the contribution of locally rare species to tree community functional richness using multi‐ and univariate approaches. We also quantified the spatial aggregation of individuals within species at several spatial scales as it relates to abundance. Results Locally rare tree species in temperate and tropical forests tended to be functionally unique and are consistently spatially clustered. Furthermore, there is no evidence that this pattern is driven by pioneer species being locally rare. Main conclusions This evidence shows that locally rare tree species disproportionately contribute to community functional richness, and we can therefore reject the hypothesis that locally rare species are suppressed by ecologically similar, but numerically dominant, species. Rather, locally rare species are likely to be specialists on spatially rare habitats or they may be ill‐suited to the locally available environments.

Influence of Local, Landscape, and Regional Variables on Sedge and Marsh Wren Occurrence in Great Lakes Coastal Wetlands - Hannah G. Panci; Gerald J. Niemi; Ronald R. Regal; Douglas C. Tozer; Thomas M. Gehring; Robert W. Howe; Christopher J. Norment (Wetlands, 2017)

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

Tree‐mycorrhizal associations detected remotely from canopy spectral properties - Joshua B. Fisher; Sean Sweeney; Edward R. Brzostek; Tom P. Evans; Daniel J. Johnson; Jonathan A. Myers; Norman A. Bourg; Amy T. Wolf; Robert W. Howe; Richard P. Phillips (Global Change Biology, 2016)
A central challenge in global ecology is the identification of key functional processes in ecosystems that scale, but do not require, data for individual species across landscapes. Given that nearly all tree species form symbiotic relationships with one of two types of mycorrhizal fungi – arbuscular mycorrhizal ( AM ) and ectomycorrhizal ( ECM ) fungi – and that AM ‐ and ECM ‐dominated forests often have distinct nutrient economies, the detection and mapping of mycorrhizae over large areas could provide valuable insights about fundamental ecosystem processes such as nutrient cycling, species interactions, and overall forest productivity. We explored remotely sensed tree canopy spectral properties to detect underlying mycorrhizal association across a gradient of AM ‐ and ECM ‐dominated forest plots. Statistical mining of reflectance and reflectance derivatives across moderate/high‐resolution Landsat data revealed distinctly unique phenological signals that differentiated AM and ECM associations. This approach was trained and validated against measurements of tree species and mycorrhizal association across ~130 000 trees throughout the temperate United States. We were able to predict 77% of the variation in mycorrhizal association distribution within the forest plots ( P

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Stochastic dilution effects weaken deterministic effects of niche‐based processes in species rich forests - Xugao Wang; Thorsten Wiegand; Nathan J. B. Kraft; Nathan G. Swenson; Stuart J. Davies; Zhanqing Hao; Robert Howe; Yiching Lin; Keping Ma; Xiangcheng Mi; Sheng‐Hsin Su; I‐Fang Sun; et al. (Ecology, 2016)
Recent theory predicts that stochastic dilution effects may result in species‐rich communities with statistically independent species spatial distributions, even if the underlying ecological processes structuring the community are driven by deterministic niche differences. Stochastic dilution is a consequence of the stochastic geometry of biodiversity where the identities of the nearest neighbors of individuals of a given species are largely unpredictable. Under such circumstances, the outcome of deterministic species interactions may vary greatly among individuals of a given species. Consequently, nonrandom patterns in the biotic neighborhoods of species, which might be expected from coexistence or community assembly theory (e.g., individuals of a given species are neighbored by phylogenetically similar species), are weakened or do not emerge, resulting in statistical independence of species spatial distributions. We used data on phylogenetic and functional similarity of tree species in five large forest dynamics plots located across a gradient of species richness to test predictions of the stochastic dilution hypothesis. To quantify the biotic neighborhood of a focal species we used the mean phylogenetic (or functional) dissimilarity of the individuals of the focal species to all species within a local neighborhood. We then compared the biotic neighborhood of species to predictions from stochastic null models to test if a focal species was surrounded by more or less similar species than expected by chance. The proportions of focal species that showed spatial independence with respect to their biotic neighborhoods increased with total species richness. Locally dominant, high‐abundance species were more likely to be surrounded by species that were statistically more similar or more dissimilar than expected by chance. Our results suggest that stochasticity may play a stronger role in shaping the spatial structure of species rich tropical forest communities than it does in species poorer forests. These findings represent an important step towards understanding the factors that govern the spatial configuration of local biotic communities. The stochastic dilution effect is a simple geometric mechanism that can explain why species’ spatial distributions in species‐rich communities approximate independence from their biotic neighborhood, even if deterministic niche processes are in effect.

Mechanisms underlying local functional and phylogenetic beta diversity in two temperate forests - Xugao Wang; Thorsten Wiegand; Nathan G. Swenson; Amy T. Wolf; Robert W. Howe; Zhanqing Hao; Fei Lin; Ji Ye; Zuoqiang Yuan (Ecology, 2015)
Although trait information has been widely used to explore underlying mechanisms of forest community structure, most studies have focused on local patterns of phylogenetic or functional alpha diversity. Investigations of functional beta diversity, on the other hand, have not been conducted at local scales in a spatially explicit way. In this study, we provide a powerful methodology based on recent advances in spatial point pattern analysis using fully mapped data of large and small trees in two large temperate forest plots. This approach allowed us to assess the relative importance of different ecological processes and mechanisms for explaining patterns of local phylogenetic and functional beta diversity. For both forests and size classes, we found a clear hierarchy of scales: habitat filtering accounted for patterns of phylogenetic and functional beta diversity at larger distances (150–250 m), dispersal limitation accounted for the observed decline in beta diversity at distances below 150 m, and species interactions explained small departures from functional and phylogenetic beta diversity at the immediate plant‐neighborhood scale (below 20 m). Thus, both habitat filtering and dispersal limitation influenced the observed patterns in phylogenetic and functional beta diversity at local scales. This result contrasts with a previous study from the same forests, where dispersal limitation alone approximated the observed species beta diversity for distances up to 250 m. In addition, species interactions were relatively unimportant for predicting phylogenetic and functional beta diversity. Our analysis suggests that phylogenetic and functional beta diversity can provide insights into the mechanisms of local community assembly that are missed by studies focusing exclusively on species beta diversity.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Conspecific negative density‐dependent mortality and the structure of temperate forests - Daniel J. Johnson; Norman A. Bourg; Robert Howe; William J. McShea; Amy Wolf; Keith Clay (Ecology, 2014)
Factors that control tree seedling dynamics are critical determinants of forest diversity. We examined the role of density‐dependent mortality and abiotic factors in the differential establishment and survival of tree seedlings at three, large, mapped forest plots in Indiana, Virginia, and Wisconsin, USA. We tested whether seedling densities and seedling survival are related to local biotic and abiotic factors with generalized linear mixed models. Spatial point pattern analyses were utilized to determine if the distribution patterns of seedlings and saplings are consistent with a pattern generated by negative density‐dependent mortality with respect to conspecific trees. Initial sampled seedling density for nearly a third of species showed a positive correlation with increasing conspecific basal area, indicating dispersal limitation, but few had any association with abiotic variables. By contrast, survival of seedlings over one year significantly declined with increasing conspecific basal area. Point pattern analyses indicated that nearly one‐third of tree species had significantly over‐dispersed point patterns of conspecific seedlings and saplings relative to adult densities; the majority of other species exhibited random spatial arrangements. Our results demonstrate that negative conspecific density‐dependent mortality of seedlings could generate the spatial patterns observed at later life stages. By differentially favoring seedlings of other species, this process may contribute to the maintenance of tree diversity in temperate forests, just as others have demonstrated for tropical forests.

Is the trend in primary penile cancer in England real? - Morten Frisch; Robert S. Van Howe (Cancer Causes & Control, 2014)

Phylogenetic and functional alpha and beta diversity in temperate and tropical tree communities - Nathan G. Swenson; David L. Erickson; Xiangcheng Mi; Norman A. Bourg; Jimena Forero-Montaña; Xuejun Ge; Robert Howe; Jeffrey K. Lake; Xiaojuan Liu; Keping Ma; Nancai Pei; Jill Thompson; et al. (Ecology, 2012)
The study of biodiversity has tended to focus primarily on relatively information‐poor measures of species diversity. Recently, many studies of local diversity (alpha diversity) have begun to use measures of functional and phylogenetic alpha diversity. Investigations into the phylogenetic and functional dissimilarity (beta diversity) of communities have been far less numerous, but these dissimilarity measures have the potential to infer the mechanisms underlying community assembly and dynamics. Here, we relate levels of phylogenetic and functional alpha diversity to levels of phylogenetic and functional beta diversity to infer the mechanism or mechanisms responsible for the assembly of tree communities in six forests located in tropical and temperate latitudes. The results show that abiotic filtering plays a role in structuring local assemblages and governing spatial turnover in community composition and that phylogenetic measures of alpha and beta diversity are not strong predictors of functional alpha and beta diversity in the forests studied.

Mass-Spring Model for Simulation of Heart Valve Tissue Mechanical Behavior - Peter E. Hammer; Michael S. Sacks; Pedro J. del Nido; Robert D. Howe (Annals of Biomedical Engineering, 2011)

Surface texture can bias tactile form perception - Masashi Nakatani; Robert D. Howe; Susumu Tachi (Experimental Brain Research, 2011)

Tissue stretch induces nuclear remodeling in connective tissue fibroblasts - Helene M. Langevin; Kirsten N. Storch; Robert R. Snapp; Nicole A. Bouffard; Gary J. Badger; Alan K. Howe; Douglas J. Taatjes (Histochemistry and Cell Biology, 2010)

County-level poverty and distant stage cancer in the United States - Robert T. Greenlee; Holly L. Howe (Cancer Causes & Control, 2009)

Cigarette smoking, body mass index, gastro-esophageal reflux disease, and non-steroidal anti-inflammatory drug use and risk of subtypes of esophageal and gastric cancers by P53 overexpression - Jonine D. Figueroa; Mary Beth Terry; Marilie D. Gammon; Thomas L. Vaughan; Harvey A. Risch; Fang-Fang Zhang; David E. Kleiner; William P. Bennett; Christine L. Howe; Robert Dubrow; Susan T. Mayne; Joseph F. Fraumeni; et al. (Cancer Causes & Control, 2009)

Usage of an early warning and information system Web-site for real-time seismicity in Iceland - Deanne Bird; Matthew J. Roberts; Dale Dominey-Howes (Natural Hazards, 2008)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Integrated Measures of Anthropogenic Stress in the U.S. Great Lakes Basin - Nicholas P. Danz; Gerald J. Niemi; Ronald R. Regal; Tom Hollenhorst; Lucinda B. Johnson; JoAnn M. Hanowski; Richard P. Axler; Jan J. H. Ciborowski; Thomas Hrabik; Valerie J. Brady; John R. Kelly; John A. Morrice; et al. (Environmental Management, 2007)